Peripheral biomarkers of oxidative stress and their limited potential in evaluation of clinical features of Huntington's patients. (September 2014) - Ciancarelli, Irene; De Amicis, Daniela; Di Massimo, Caterina; Di Scanno, Carla; Pistarini, Caterina; D'Orazio, Nicolantonio; Tozzi Ciancarelli, Maria Giuliana
Abstract Context: Peripheral oxidative biomarkers could be useful for monitoring clinical features of Huntington's disease (HD). Materials and methods: Cu/Zn-superoxide dismutase (Cu/Zn-SOD), neuron-specific enolase (NSE) and 8-hydroxy-2′-deoxyguanosine (8-oxoGua) serum levels were analysed in 18 HD patients and 10 controls. Clinical measures were recorded from each HD patients. Results: Cu/Zn-SOD, NSE and 8-oxoGua values were higher in HD patients than in controls. Cu/Zn-SOD and NSE correlated positively. No correlation was observed between the biomarkers analysed and the clinical measures assessed. Discussion and conclusion: Serum oxidative biomarkers could express the neuronal oxidative processes going on in HD patients but are inadequate to evaluate clinical features of the disease.